Psychological Courage - Putman, Daniel (Hamilton Books, 2004)
In this book, Daniel Putman outlays three forms of courage: physical, mental, and psychological. He defines psychological courage as the courage to face addictions, phobias, and obsessions, and to avoid self deception and admit mistakes. This book analyzes what psychological courage is and upholds it as a central virtue for human happiness.